2011
DOI: 10.1371/journal.pone.0017021
|View full text |Cite
|
Sign up to set email alerts
|

Segregation of Fluorescent Membrane Lipids into Distinct Micrometric Domains: Evidence for Phase Compartmentation of Natural Lipids?

Abstract: BackgroundWe recently reported that sphingomyelin (SM) analogs substituted on the alkyl chain by various fluorophores (e.g. BODIPY) readily inserted at trace levels into the plasma membrane of living erythrocytes or CHO cells and spontaneously concentrated into micrometric domains. Despite sharing the same fluorescent ceramide backbone, BODIPY-SM domains segregated from similar domains labelled by BODIPY-D-e-lactosylceramide (D-e-LacCer) and depended on endogenous SM.Methodology/Principal FindingsWe show here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 54 publications
3
30
0
Order By: Relevance
“…The latter observation also indicated that patches revealed by CTxB were not induced by exogenous GM1BODIPY insertion. These results supported the interpretation that micrometric BODIPY lipid domains could refl ect endogenous lipid compartmentation, as previously suggested for BODIPY-SM domains in CHO cells based on endogenous SM depletion ( 19,20 ).…”
Section: Labeling Of Endogenous Gm1 By Cholera Toxin Also Reveals Subsupporting
confidence: 90%
See 4 more Smart Citations
“…The latter observation also indicated that patches revealed by CTxB were not induced by exogenous GM1BODIPY insertion. These results supported the interpretation that micrometric BODIPY lipid domains could refl ect endogenous lipid compartmentation, as previously suggested for BODIPY-SM domains in CHO cells based on endogenous SM depletion ( 19,20 ).…”
Section: Labeling Of Endogenous Gm1 By Cholera Toxin Also Reveals Subsupporting
confidence: 90%
“…IIIB). Thus, cholesterol depletion specifi cally impaired the less-packed BODIPY-PC and BODIPY-SM domains and spared the mostpacked BODIPY-GlcCer domains, packing of domains being previously suggested by the propensity of BODIPYlipids to form excimers ( 20 ). To further test whether cholesterol depletion could instead favor other domains, we looked at the artifi cial dialkylindocarbocyanine DiIC18, a well-established membrane probe that homogenously labels untreated RBCs ( 19,42 ), but which is recognized to preferentially partition into the liquid-disordered phase in giant unilamellar vesicles, segregated from the liquid-ordered phase decorated by fl uor escent cholera toxin that binds ganglioside GM1 ( 8 ).…”
Section: The High Cholesterol Level Of Rbcs Promotes Bodipy-sm and Bomentioning
confidence: 72%
See 3 more Smart Citations